The Children in Action Pilot Study - Theresa A. Nicklas, Theresa A.; Nguyen, Tuan; Butte, Nancy F.; Liu, Yan (International Journal of Child Health and Nutrition, 2013)
Interventions that can successfully alter the trajectory toward obesity among high-risk children are critical if we are to effectively address this public health crisis. The goal of this pilot study was to implement and evaluate an innovative physical activity program with Hispanic-American (HA) preschool children attending Head Start. The Children in Action (CIA) program was a five month physical activity intervention. This intervention was a pilot study with 3- to 5-year-olds enrolled in four HA Head Start centers. After baseline assessment, centers were matched by enrollment and randomly assigned to either the intervention or the control condition. A total of 295 preschool children were randomly selected across the four centers. The primary endpoints of this study were favorable changes in physical activity levels and gross motor skills. Using mixed effect time-series regression models, changes in weight was a secondary endpoint. We did not observe a statistical difference between intervention and control groups in physical activity levels during the awake time, gross motor skills, or weight status. Process evaluation data showed that there was adherence to protocols and the intervention was delivered 92% of the time, four times per week, during the five month intervention. We demonstrated that it is feasible to conduct the SPARK-Early Childhood (EC) curriculum among preschool children attending Head Start centers but that an increased dose and/or longer intervention duration will be required to impact gross motor skills, physical activity levels and weight status during this critical early childhood development stage.